Indonesia : Implementing National Policies in a Decentralized Context; Special Purpose Programs to Protect the Poor - Ahmad, Ehtisham (IMF Working Papers; Working Paper, 2000)
In the context of continuing adjustments in the economy, the Government of Indonesia proposes to bring energy prices closer to long run marginal cost, while adequately compensating the poor. We focus on the constraints on central government policy objectives towards the poor as decentralization takes effect. However, local governments currently lack credible social protection instruments and their objectives usually do not match those of the center, which imposes constraints on program designs. We discuss the suitability of a number of safety net mechanisms in a decentralized context and draw policy implications.